Ground-based parallax confirmed by Spitzer: binary microlensing event MOA-2015-BLG-020 - Wang, Tianyu; Tsapras, Yiannis; Hundertmark, Markus; Wambsganß, Joachim; Schmidt, Robert W. (The astrophysical journal, 2017)
We present the analysis of the binary gravitational microlensing event MOA-2015-BLG-020. The event has a fairly long timescale (∼63 days) and thus the light curve deviates significantly from the lensing model that is based on the rectilinear lens-source relative motion. This enables us to measure the microlensing parallax through the annual parallax effect. The microlensing parallax parameters constrained by the ground-based data are confirmed by the Spitzer observations through the satellite parallax method. By additionally measuring the angular Einstein radius from the analysis of the resolved caustic crossing, the physical parameters of the lens are determined. It is found that the binary lens is composed of two dwarf stars with masses ##IMG## [http://ej.iop.org/images/0004-637X/845/2/129/apjaa813bieqn1.gif] $M_1=0.606± 0.028\,M_ødot $ and ##IMG## [http://ej.iop.org/images/0004-637X/845/2/129/apjaa813bieqn2.gif] $M_2=0.125\,± 0.006\,M_ødot $ in the Galactic disk. Assuming that the source star is at the same distance as the bulge red clump stars, we find the lens is at a distance ##IMG## [http://ej.iop.org/images/0004-637X/845/2/129/apjaa813bieqn3.gif] $D_L=2.44± 0.10\,\mathrmkpc$ . We also provide a summary and short discussion of all of the published microlensing events in which the annual parallax effect is confirmed by other independent observations.
Gesehen am 15.09.2017